Moral Dilemmas in Hospitals: Which Shooting Victim Should Be Saved? - Navarick, Douglas J.; Moreno, Kristen M. (Frontiers in Psychology, 2022)
Moral judgments can occur either in settings that call for impartiality or in settings that allow for partiality. How effective are impartiality settings such as hospitals in suppressing personal biases? Portrayed as decision-makers in an emergency department, 431 college students made judgments on which of two victims of a mass shooting should receive immediate, life-saving care. Patients differed in ways that could reveal biases, e.g., age (8 vs. 80 years), kinship (stranger vs. cousin), gender (female vs. male), and villain/hero (shooter vs. policeman who stopped him). Participants rated each patient’s moral deservingness to receive immediate care and the likelihood they would choose the patient. Both scales showed young favored over old, cousin (or daughter) over stranger, and policeman over shooter (largest difference). In a hospital-room scenario with high risk of injury from falling, age bias disappeared. With moderate fall risk, age bias reversed and kinship deservingness bias disappeared. Bias decreases when there is a decrease in severity of potential harm to the preferred stakeholder. Settings that call for impartiality are not reliable “boundary conditions” against expressions of bias. In the absence of explicit guidelines for allocating scarce resources, a systematic, objective method of random selection offers a potentially useful strategy.